THE INFLUENCE OF ONLINE ADVERTISING ON THE PURCHASING DECISIONS OF HOMEMAKERS IN JAIPUR CITY - Prajapat, Sunita; Shrivastava, Garima (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The rapid growth of digital technology and the widespread adoption of the Internet have significantly altered consumer behavior, particularly among homemakers in urban areas. As the digital landscape evolves, it has reshaped the way individuals access information, interact with brands, and make purchasing decisions. This transformation is especially pronounced among homemakers, who are increasingly turning to online platforms to manage household responsibilities and make informed choices about products and services. This research paper examines the influence of online advertising on the purchasing decisions of homemakers in Jaipur City, a rapidly urbanizing region in India. Homemakers play a pivotal role in household purchases, making them a critical demographic for marketers to target. Traditionally seen as the primary decision-makers for a wide range of household needs—from groceries and daily essentials to larger investments like electronics and home furnishings—homemakers are now also engaging with digital content that influences their choices. The study explores how various forms of online advertising, including social media advertisements, search engine marketing, and e-commerce promotions, impact their buying behavior. The data was collected through structured questionnaires and in-depth interviews. The questionnaires focused on online shopping frequency, types of products purchased, brand preferences, and the influence of online ads on homemakers in Jaipur. This study aims to understand how online advertisements influences homemaker’s choices. This research underscores the importance of understanding the unique preferences and behaviors of homemakers to optimize digital marketing strategies.